Prescription patterns of Antibiotics in Acute tonsillitis: Hospital-based study - Sigdel, Brihaspati; Dubey, Tulika; Nepali, Rajendra; KC, Neeraj (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Acute tonsillitis is caused by either viruses or bacteria and is characterized by a sore throat and painful swallowing. About 49% of cases are thought to be caused by Group A beta-hemolytic streptococci. Penicillin should be given empirically after the diagnosis of acute tonsillitis. This study was carried out to find out the prescription pattern of antibiotics among the admitted cases of acute tonsillitis. Materials and Methods: This study was conducted in the Department of Otorhinolaryngology and Head and Neck Surgery, Gandaki Medical College Teaching Hospital and Research Centre (GMCTH), Pokhara. All the patients who were admitted for acute tonsillitis in the ENT ward were enrolled in this study. Age, gender, the average number of drugs per prescription, and the most commonly prescribed drug was recorded. Results: There were 320 patients with acute tonsillitis and the mean age was 27.44 ± 11.1 years. Most of the cases were in their twenties. The average number of drugs per prescription was four while the total number of antibiotics used was 520. The single antibiotic was used in 170 (53%) cases and a two-drug combination was used in 91(28.4%) cases. Ceftriaxone was the most commonly prescribed drug. There were 78 (24.3%) cases under monotherapy and 69 (21%) in multitherapy. Conclusion: Among the various effective antimicrobials, ceftriaxone was the most commonly prescribed antimicrobial. The injectable route of antibiotics administration was a widely used method in hospitalized patients in our setting.